2018
DOI: 10.1128/aac.02378-17
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mcr-1 Gene among Escherichia coli Isolates from Farmed Fish and Characterization of mcr-1 -Bearing IncP Plasmids

Abstract: The presence of the gene in isolated from retail freshwater fish was investigated. Seven (3.65%) clonally unrelated original isolates from grass carp were positive for The genes were encoded by either chromosomes ( = 2) or conjugative plasmids (2 IncI2, 2 IncP, and 1 IncX4). The IncP plasmids were similar to other -harboring IncP plasmids from China, though the insertion sites varied. Our report warrants further surveillance of resistance genes in aquaculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Furthermore, this sequence type has been associated with the global carriage of ESBL-producing E. coli [13,34,48]. E. coli ST156 was identified in fish [50], canines, felines, horses [51], chickens, and other avian species [52,53]. Lastly, this study is the first demonstration of ST1380 E. coli being isolated from equines, the sequence type that was previously isolated from swine and bovine species [54,55].…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, this sequence type has been associated with the global carriage of ESBL-producing E. coli [13,34,48]. E. coli ST156 was identified in fish [50], canines, felines, horses [51], chickens, and other avian species [52,53]. Lastly, this study is the first demonstration of ST1380 E. coli being isolated from equines, the sequence type that was previously isolated from swine and bovine species [54,55].…”
Section: Discussionmentioning
confidence: 55%
“…MLST analysis of the sequenced genomes showed that F1 and F2 belonged to sequence types, ST48 and ST101, respectively. These STs have been associated with mcr and multidrug resistant strains and occur in a variety of niches and hosts, including humans, avian hosts, and fish [ 23 , 64 , 65 , 66 ]. This highlighted the ability of mcr-1 to spread to important matrices and hosts and suggested that F1 and F2 isolates can be transmitted beyond the trout farm and/or can be acquired by the fish from other polluted sources [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted on integrated fish-duck farming, it was suggested that E. coli harboring the mcr-1 can spread from aquatic animals to affect the supply chain and humans [ 24 ]. Therefore, the detection of mcr-1.1 in fish poses a significant public health concern, because resistance can be potentially transmitted to pathogens that affect humans and other animals [ 23 , 24 ]. Additionally, international trade with farmed fish can act as a route for the dissemination of mcr between countries [ 18 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations